2023
DOI: 10.1002/gps.5919
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation among people with Parkinson's disease and comparison with a control group

Abstract: Background: Detection of suicidal ideation (SI) is key for trying to prevent suicide.The aim of this study was to analyze the frequency of SI and related factors in Spanish people with Parkinson's Disease (PwPD) and to compare them with a control group.Methods: PD patients and controls recruited from the Spanish cohort COPPADIS from January 2016 to November 2017 were included. Two visits were conducted: V0 (baseline); V2 (2-year � 1 month follow-up). SI was defined as a score ≥1 on item nine of the Beck Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Among these, 15 studies were cross-sectional studies, 8 were retrospective cohort studies, and 3 were case-control studies. Santos-Garcia et al used a prospective cohort design, while Kostic et al used both cross-sectional and cohort study designs. Only 3 of the studies reported a follow-up period: Kostic et al reported that the patients were followed up with for 8 years, Lee et al reported a mean follow-up time of 7.1 (SD, 4.1) years, and Santos-Garcia et al reported that patients were followed up for 2 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 15 studies were cross-sectional studies, 8 were retrospective cohort studies, and 3 were case-control studies. Santos-Garcia et al used a prospective cohort design, while Kostic et al used both cross-sectional and cohort study designs. Only 3 of the studies reported a follow-up period: Kostic et al reported that the patients were followed up with for 8 years, Lee et al reported a mean follow-up time of 7.1 (SD, 4.1) years, and Santos-Garcia et al reported that patients were followed up for 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…Influence analysis revealed 3 outliers: Merschdorf et al, Santos-Garcia et al, and Dissanayaka et al A sensitivity analysis excluding them was conducted and found the prevalence to be 24.0% (95% CI, 19.1-29.7). The I 2 index was 89.0% and the Cochran Q test was significant at P < .001.…”
Section: Resultsmentioning
confidence: 99%